Imaging Heterogeneously Distributed Photo‐Active Traps in Perovskite Single Crystals. Issue 13 (19th February 2018) - Yuan, Haifeng; Debroye, Elke; Bladt, Eva; Lu, Gang; Keshavarz, Masoumeh; Janssen, Kris P. F.; Roeffaers, Maarten B. J.; Bals, Sara; Sargent, Edward H.; Hofkens, Johan
Abstract: Organic–inorganic halide perovskites (OIHPs) have demonstrated outstanding energy conversion efficiency in solar cells and light‐emitting devices. In spite of intensive developments in both materials and devices, electronic traps and defects that significantly affect their device properties remain under‐investigated. Particularly, it remains challenging to identify and to resolve traps individually at the nanoscopic scale. Here, photo‐active traps (PATs) are mapped over OIHP nanocrystal morphology of different crystallinity by means of correlative optical differential super‐resolution localization microscopy (Δ‐SRLM) and electron microscopy. Stochastic and monolithic photoluminescence intermittency due to individual PATs is observed on monocrystalline and polycrystalline OIHP nanocrystals. Δ‐SRLM reveals a heterogeneous PAT distribution across nanocrystals and determines the PAT density to be 1.3 × 10 14 and 8 × 10 13 cm −3 for polycrystalline and for monocrystalline nanocrystals, respectively. The higher PAT density in polycrystalline nanocrystals is likely related to an increased defect density. Moreover, monocrystalline nanocrystals that are prepared in an oxygen‐ and moisture‐free environment show a similar PAT density as that prepared at ambient conditions, excluding oxygen or moisture as chief causes of PATs. Hence, it is concluded that the PATs come from inherent structural defects in the material, which suggests that the PAT density can be reduced by improving crystalline quality of the material. Abstract : Optical differential super‐resolution localization microscopy maps the heterogeneous distribution of photoactive traps in organic–inorganic lead halide perovskite nanocrystals by contrast of photoluminescence intermittency. The reconstructed trap distribution is correlated with the morphology and crystallinity of nanocrystals. The higher average trap density revealed in polycrystalline nanocrystals indicates that the traps are correlated with structural defects.